"Essential" migrants: Evidence from the 2020 H-2B visa lottery - Parag Mahajan (W.E. Upjohn Institute for Employment Research, 2025)
I study how access to foreign-born workers impacts firms and local economics in times of acute crisis. The 2020 H-2B visa lottery randomly gave some U.S. firms the chance to hire low-wage, migrant workers during the height of the COVID-19 pandemic. Using administrative data across three government agencies, I find that access to H-2B workers led to decreased business closures, increased revenues, increased payroll, and increased employment in 2020. I also find suggestive evidence that these effects spilled over to non-participant firms within the same county.
Keywords: J23; F22; J61; 330; migrant workers; H-2B visa; COVID-19 pandemic; firm dynamics